Use of every ten-day criteria for metabolic profile test after calving and dry off in dairy herds - Kida, K. (Large Animal Clinic and Research Center, Ebetsu, Hokkaido (Japan)) (Journal of Veterinary Medical Science, 2002)
The traditional metabolic profile test cannot be applied to peripartum dairy cows, because these cows are in a state of physiological abnormality making it difficult to interpret their blood components. This study aimed at establishing and evaluating the practicability of interpreting a metabolic profile test every 10 days (Ten-day criteria) during the dry and lactation periods in herds with high and no incidence of peripartum diseases. Data from 29,043 cows in 1,130 commercial dairy herds were used to establish standard values every 10 days, mean ± 1.0 standard deviation for the metabolic profile test. The practicability of these criteria was evaluated in herds with peripartum diseases. In the ten-day criteria, the body condition score, albumin, blood urea nitrogen, glucose, total cholesterol, nonesterified fatty acids, γ-glutamyl transpeptidase and aspartate aminotransferase, fluctuated during the dry and early lactation periods and there were very big changes in packed cell volume, blood urea nitrogen, total cholesterol and magnesium just after calving. The ten-day criteria were able to detect overconditioned cows, low levels of albumin, total cholesterol and magnesium, and high nonesterified fatty acids in herds with a high incidence of peripartum diseases. In conclusion, the ten-day criteria can be successfully applied to peripartum cows, and is recommended because it is able to detect metabolic abnormalities not only in the herd, but also in individual cows.